The Relationship Between Service Quality, Brand Image, Price Fairness, Customer Satisfaction, and Customer Loyalty at Ren Coffee and Eatery Coffee Shop - Syaefulloh, Syaefulloh (Dinasti Publisher, 2025)
Any business around the world depends on customers, therefore it is important to treat customers well. With the current very tight competitive situation, the coffee shop business continues to provide superior service quality and a very good brand image that is perceived by customers to gain customer satisfaction and customer loyalty. This research aims to determine the relationship between service quality, brand image, price fairness, customer satisfaction and customer loyalty. This research uses casual associative analysis which analyses the statistical relationship between one variable and another variable and uses the Partial Least Square Structural Equating Modelling (PLS-SEM) analysis method. The results of this research both show that service quality has a positive effect on brand image and customer satisfaction but has a negative effect on customer loyalty. Brand image has a positive effect on customer satisfaction and customer loyalty. Price fairness has a positive effect on customer satisfaction and customer satisfaction has a positive effect on customer loyalty. Based on the research results, it was found that service quality must continue to be improved because it can influence brand image and a stronger brand image can influence customer loyalty and customer satisfaction.